2015
DOI: 10.1111/1755-5922.12148
|View full text |Cite
|
Sign up to set email alerts
|

New Fixed‐Dose Combinations of Fenofibrate/Simvastatin Therapy Significantly Improve the Lipid Profile of High‐Risk Patients with Mixed Dyslipidemia Versus Monotherapies

Abstract: SUMMARYAims: Guidelines propose additional therapy to statin to treat elevated triglycerides (TG) and low high-density lipoprotein cholesterol (HDLC) in dyslipidemic patients. We evaluated the effects of new fixed-dose combinations (FDC) of fenofibrate/simvastatin on plasma lipids versus simvastatin or fenofibrate monotherapies. Methods: Subjects with mixed dyslipidemia at high or very high cardiovascular risk on stable statin therapy for at least 3 months were included in a randomized, double-blind, active-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(16 reference statements)
0
10
0
Order By: Relevance
“… 70 Outstanding results can be obtained with a new fixed-dose combination with fenofibrate 145 mg in a new nanotechnology formulation compared to single medications. 71 As observable from all the studies referred, the higher the baseline dyslipidemia level, the better the effect of combined drugs is.…”
Section: Combination Therapymentioning
confidence: 98%
“… 70 Outstanding results can be obtained with a new fixed-dose combination with fenofibrate 145 mg in a new nanotechnology formulation compared to single medications. 71 As observable from all the studies referred, the higher the baseline dyslipidemia level, the better the effect of combined drugs is.…”
Section: Combination Therapymentioning
confidence: 98%
“…A total of 20,176 patients were included in the eligible studies, 10,249 in the intervention arm and 9841 in the comparator arm while 86 patients received both interventions in the setting of crossover studies. The majority of the studies (n = 21) had examined fenofibrate alone or in combination [7,8,14,15,17,18,[20][21][22][24][25][26][27][28][29][30][31][33][34][35]40,41] and 11 of them fenofibrate vs. placebo [8,14,15,17,18,26,27,31,34,35]. Among the included studies more than half of the participants came from the FIELD and the ACCORD studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The characteristics of the included studies are available in Table 1. Nineteen studies (reported in 24 articles) met the inclusion criteria [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], and allocated a total of 7619 participants to either statin or fibrate monotherapy, totaling approximately 4745 person-years of follow-up. Five studies [31,33,[36][37][38] had a follow-up duration of 24 weeks or longer, and the longest follow-up was two years [38].…”
Section: Description Of Studies and Patient Populationmentioning
confidence: 99%
“…Because of the small number of events and different outcome descriptions, we could not pool studies for the outcome of kidney injury. Three studies reported kidney injury related outcomes as renal failure [30,43], renal impairment [27], or renal dysfunction [36]. A total of four cases of kidney injury were reported in the fibrate group and zero in the statin group.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation